Regional variations of banking services and poverty reduction: Evidence from subdistrict level administrative data of Bangladesh - Kazi Iqbal; Paritosh K. Roy; A. K. Shamsul Alam (Asian Development Bank Institute (ADBI), 2018)
While the role of commercial banks in financing economic growth and reducing poverty and income inequality is well documented in cross-country setup, the regional variations of the banking services within a country and its association with poverty reduction is understudied. Understanding of the local-level variations of banking services is essential for deeper understanding of financial inclusion and its impact on local-level poverty. To this end, we first shed light on the regional variations of a host of banking variables by creating a "banking atlas" using administrative data that captures the access to and use of banking services at the sub-district level in Bangladesh. The maps, uncovering interesting regional peculiarities, have the potential to be an important policy tool for targeting lagging regions and designing customized regional interventions in developing countries. Next, we link regional mapping of banking variables to the incidence of poverty using descriptive statistics and regression models. The regression results demonstrate that access to banking services is strongly associated with poverty reduction, even in the rural sample. However, in the case of use of banking services, the amount of deposit has a strong impact on poverty reduction but the amount of credit per adult is found to have no significant impact. These results corroborate the growing evidence that greater access to deposit services can promote saving and increase income. This study also highlights the importance of using administrative data to monitor local-level development.
Keywords: O16; I32; G21; 330; banking maps; financial inclusion; regional targeting; poverty reduction; Bangladesh